Induction of labor in elderly nulliparous women. (17th September 2017) - Hadar, Eran; Hiersch, Liran; Ashwal, Eran; Chen, Rony; Wiznitzer, Arnon; Gabbay-Benziv, Rinat
Abstract: Purpose : Maternal age is an important consideration for antenatal care, labor and delivery. We aimed to evaluate the induction of labor (IoL) failure rates among elderly nulliparous women. Materials and methods : We conducted a retrospective analysis of all nulliparous women at 34 + 0 to 41 + 6 weeks, undergoing cervical ripening by prostaglandin E2 (PGE2) vaginal insert. Study group included elderly (≥35 years) nulliparous and control group included non-elderly (<35 years) nulliparous women. Primary outcome was IoL failure rate and secondary outcome was cesarean delivery rate. Outcomes were compared between the groups by univariate analysis followed by regression analysis to adjust results to potential confounders. Results : Of 537 women undergoing IoL, 69 (12.8%) were elderly. The univariate analysis demonstrated no difference in IoL failure rate (26.5% versus 34.8%, p = 0.502) between groups. However, elderly nulliparous women had higher rates of cesarean delivery (36.2% versus 21.4%, p = 0.009). This difference was no longer significant after adjustment for maternal body mass index, indication for delivery, birth weight and gestational age at delivery. Conclusion : Among nulliparous women, older maternal age is not associated with higher rates of IoL failure or cesarean deliveries.